Increasing the Spirit of Defending the Country through Citizenship Education in Higher Education - Yudha Pradana; Andriyana Andriyana (Pancasila: Jurnal Keindonesiaan, 2022)
Defending the state is the right as well as the obligation of citizens. Nevertheless, defending the state is often simplified as militaristic, but it can also be done through formal educational means. Civic Education (PKn) is one medium to develop the spirit of defending the state. This article attempts to examine the mapping of the linear values ​​of state defense with Civic Education (PKn) subject in university. This research uses a qualitative approach with literature study and documentation study. The results show that the value of state defense in Civic Education (PKn) is the value of love of the homeland which is learned through the material of national identity and the insight of the archipelago; the values ​​of national and state consciousness which are learned through the obligations and rights of the state and citizens, the constitutional values ​and norms of the 1945 Constitution of the Republic of Indonesia, and the democracy of Indonesia; loyalty to Pancasila as state ideology is learned through the material of Pancasila; and the value of sacrificing for the nation and state are taught through law enforcement materials that are just and national defense and state defense. While learning is designed to actualize the values ​​of state defense through cooperative learning, inquiry, and contextual learning.